2009
DOI: 10.3945/ajcn.2008.27441
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention for blood pressure control: a call for action!

Abstract: Observational studies have shown the relation between blood pressure (BP) and several nutrients, including protein, fiber, potassium, magnesium, and calcium. However, randomized intervention trials of individual nutrient supplements often have shown an inconsistent or only a small effect on BP. When 2 of these nutrients are consumed naturally together in foods at the recommended levels such as in vegetarian diets or in the Dietary Approaches to Stop Hypertension (DASH) dietary pattern, their BP effects are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several large epidemiological studies have indicated that there is an inverse relationship between dietary cereal fibre intake and risk of cardiovascular diseases 25. Furthermore, results from clinical trials have shown that higher intake of fibre can reduce blood pressure and total and low‐density lipoprotein cholesterol levels 8, 26. Without doubt, the high dietary fibre content of few‐flower wild rice could make it ready source of nutraceuticals or functional foods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several large epidemiological studies have indicated that there is an inverse relationship between dietary cereal fibre intake and risk of cardiovascular diseases 25. Furthermore, results from clinical trials have shown that higher intake of fibre can reduce blood pressure and total and low‐density lipoprotein cholesterol levels 8, 26. Without doubt, the high dietary fibre content of few‐flower wild rice could make it ready source of nutraceuticals or functional foods.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a pooled analysis of available national and regional data, Kearney et al 7 reported the overall prevalence of hypertension in 2000 to be 26.4% of the world's population and also predicted that the burden of hypertension would increase by 60% to approximately 1.56 billion in the year 2025. Previous studies have shown a relationship between blood pressure and several nutrients, including proteins, fibre, potassium, magnesium and calcium 8. Therefore, to obtain a broad understanding of their functional health benefits and nutritional value, it is necessary to conduct a comprehensive analysis of the nutritient compositions of the leaf sheaths and stems of few‐flower wild rice.…”
Section: Introductionmentioning
confidence: 99%